Blastocyst transfer: a risk factor for gestational diabetes mellitus in women undergoing in vitro fertilization - Chen, Huijun; Li, Jian; Cai, Sufen; Tang, Sha; Zeng, Suimin; Chu, Chang; Hocher, Carl-Friedrich; Rösing, Benjamin; Krämer, Bernhard; Hu, Liang; Lin, Ge; Gong, Fei; et al. (The journal of clinical endocrinology & metabolism, 2022)
The risk of developing gestational diabetes mellitus (GDM) is higher in women undergoing assisted reproductive treatment than in women conceiving spontaneously.To determine whether the GDM risk after day-3 embryo transfer differs from the GDM risk after day-5 blastocyst transfer.Prospective observational study in women becoming pregnant after first fresh embryo or blastocyst transfer.A total of 1579 women got pregnant and had live birth; 1300 women got day-3 embryo transfer only, whereas 279 women received at least 1 blastocyst. Of 1579 women, 252 developed GDM. Age, body mass index, baseline estradiol, baseline high-density lipoprotein, and progesterone on the day of human chorionic gonadotropin injection were not different in women receiving day-3 embryos only vs women receiving at least 1 blastocyst. The number and quality of retrieved oocytes were not different in women receiving day-3 embryo transfer from those receiving blastocysts. Our study confirmed already established GDM risk factors such as age and body mass index, baseline estradiol, and high-density lipoprotein, as well as progesterone after ovarian stimulation. We furthermore demonstrate that the GDM incidence in women receiving day-5 blastocyst transfer was significantly higher than those who received day-3 embryo transfer (21.15% vs 14.85%; P = 0.009). Considering confounding factors, we likewise saw that blastocyst transfer was an independent procedure-related GDM risk factor [P = 0.009, Exp (B): 1.56, 95% CI: 1.12-2.18].Blastocyst transfer after in vitro fertilization/intracytoplasmic sperm injection increases the risk of developing GDM.
Online veröffentlicht: 20 August 2021
Gesehen am 16.02.2023